A fuel oil corrosion resistant Al-Cr thin film material and its preparation method and application
The Al-Cr film prepared by non-equilibrium magnetron sputtering technology and gradient component deposition method solves the problems of low adhesion and loose structure of the Al film on the substrate surface, achieves high film/base bonding and good ductility, and is suitable for fuel-resistant oil corrosion applications in engine sealing systems.
Patent Information
- Application Number
- CN202411710289.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-04-08
AI Technical Summary
Al film materials have low adhesion on the substrate surface, loose structure, easy to fall off, and poor ductility, making it difficult to meet the requirements of engine sealing systems for fuel corrosion and ductility.
Al-Cr films were prepared by non-equilibrium magnetron sputtering technology and gradient components deposition method. By pretreating the matrix, regulating the target bombardment energy and deposition atom diffusion ability, the film/base binding force and film density were improved.
The high film/base binding force (≥30 N), structural density and good ductility of the Al-Cr film are achieved, which significantly improves its corrosion-resistant sealing and lubricating performance in the engine fuel system.
Smart Images

Figure CN119776784A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal surface modification, and in particular relates to an Al-Cr thin film material resistant to fuel oil corrosion and a preparation method and application thereof. Background Art
[0002] Al film / plating has important applications in weapon equipment movement and transmission systems due to its good ductility, electrical conductivity, thermal conductivity, heat resistance, corrosion resistance and other advantages. The metal sealing ring components used in the engine sealing system are in a fuel and gas corrosion environment for a long time, and the surface of the metal sealing ring is required to have good fuel and gas corrosion resistance and a certain ductility to protect the sealing effect of the metal sealing ring. Therefore, preparing a layer of Al film material on the surface of the metal sealing ring as a surface protective layer to improve its high-temperature corrosion resistance is an effective way. However, Al film materials usually face the disadvantages of very low film / substrate bonding, high brittleness, and loose structure. They are easy to fall off on the surface of the substrate and are difficult to meet the service requirements. This is the main technical bottleneck restricting its application. Summary of the invention
[0003] In view of this, the present invention aims to propose a fuel corrosion resistant Al-Cr film material and a preparation method and application thereof, to solve at least one problem in the background technology. The present application overcomes the difficult problems of low adhesion of Al film materials on the substrate surface, loose structure, easy falling off and poor ductility. The purpose of the present invention is to provide a fuel corrosion resistant Al-Cr film with excellent film / substrate bonding, relatively dense structure and good ductility and a preparation technology thereof, so as to realize the application of Al film in the sealing of fuel systems of high-power diesel engines in my country.
[0004] To achieve the above object, the technical solution of the present invention is achieved as follows: A fuel oil corrosion resistant Al-Cr thin film material and a preparation method and application thereof, comprising the following steps: S1: pre-treating the substrate; S2: Deposition of thin film by unbalanced magnetron sputtering technology: Under vacuum conditions, pre-sputtering is performed with Ar plasma to clean the target and substrate surfaces, followed by sputtering deposition of Al and Cr targets to a preset film thickness, followed by furnace cooling to room temperature to prepare an Al-Cr film.
[0005] Furthermore, the pretreatment of the substrate in step S1 includes ultrasonic cleaning and drying the surface of the steel substrate.
[0006] Furthermore, the pretreatment of the substrate in step S1 includes polishing the substrate, and the polished steel substrate is ultrasonically cleaned in petroleum ether, ethanol and acetone in sequence and then dried.
[0007] When coating, the surface of the workpiece to be coated must be clean and free of oil stains. There will be residual contaminants on the surface of the workpiece after processing. Petroleum ether cleaning can dissolve oil contaminants first, ethanol cleaning can dissolve other contaminants and take away particulate impurities, and acetone has a better ability to remove the very small amount of contaminants that may remain. Therefore, cleaning in this order can ensure that the surface of the workpiece is very clean and meets the requirements for the surface of the workpiece to be plated.
[0008] Furthermore, the substrate includes one of stainless steel or 9Cr18 steel.
[0009] Furthermore, in step S2, two Al targets and one Cr target disposed face to face are used to deposit the thin film by unbalanced magnetron sputtering technology, and the purity of the target materials is not less than 99.99%.
[0010] Furthermore, in step S2, Ar plasma is used for pre-sputtering cleaning of the target and substrate surface, with an argon gas flow rate of 20-30 sccm, a bias voltage of 200-400 V, an Al target current of 0.2-0.4 A, a Cr target current of 0.1-0.3 A, and a sputtering cleaning time of 30 min.
[0011] Furthermore, during film deposition, a gradient composition deposition method was used. The argon gas flow rate in the first stage was 25-40 sccm, the bias voltage was 80-140 V, and the Al target current was initially 0.1-0.5 A, which gradually increased to 0.6-1 A after 15-40 min. After another 40 to 80 minutes, the Al target current in the second stage gradually increased to 1.5 to 3 A. In the third stage, the film is deposited to a preset thickness at an argon gas flow rate of 10-30 sccm, a bias voltage of 80-140 V, an Al target current of 1.5-2.8 A, and a Cr target current of 0.1-1 A; Preferably, the preset thickness is 2-9 μm.
[0012] Furthermore, after the deposition is completed, the sample is cooled to room temperature in a high vacuum coating chamber with the furnace, and the cooling time is 3 to 5 hours.
[0013] The fuel corrosion resistant Al-Cr film prepared by the above-mentioned method for preparing a fuel corrosion resistant Al-Cr film material is characterized in that the Cr content in the fuel corrosion resistant Al-Cr film is 1~6 at.%, and the film-base bonding strength of the fuel corrosion resistant Al-Cr film is ≥30 N.
[0014] Furthermore, the fuel oil corrosion resistant Al-Cr film has a thickness of 2-9 μm and a microhardness of Hv100-200.
[0015] The fuel corrosion resistant Al-Cr film is applied to the engine sealing system.
[0016] Compared with the prior art, the fuel oil corrosion resistant Al-Cr thin film material and its preparation method and application described in the present invention have the following advantages: 1. The present invention adopts unbalanced magnetron sputtering technology to prepare Al thin film, which has the advantages of high ionization rate, uniform and consistent film formation, and no damage to the workpiece, and is particularly suitable for large-area, high-precision, and complex workpiece surface coating protection treatment.
[0017] 2. The present invention adopts a gradient component deposition method to fundamentally solve the technical difficulties of low bonding strength and easy detachment of Al film on steel substrate, and provides an effective method for forming a thin film material with strong film / substrate bonding.
[0018] 3. In the process of thin film preparation, the present invention realizes effective regulation of target bombardment energy and diffusion capacity of deposited atoms by orderly and reasonably controlling deposition parameters, thereby increasing the nucleation density of deposited atoms and thus increasing the density of the thin film.
[0019] 4. The Al film prepared by the method of the present invention has uniform composition, a film thickness of 2-9 μm, a film bonding strength greater than 30 N, a dense structure, and good ductility. It has good application prospects in corrosion-resistant sealing and lubrication of engine fuel systems. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0021] Figure 1 The surface and cross-sectional electron microscope photos of the thin Al-Cr film prepared in Example 1 of the present invention; Figure 2 The surface and cross-sectional electron microscope photos of the thick Al-Cr film prepared in Example 2 of the present invention; Figure 3 The curve of the film / substrate bonding strength of the Al-Cr film prepared in Example 2 of the present invention as a function of the loading force in the scratch test; Figure 4 for Figure 3 Optical and electron microscopic morphology images of the scratch start and end regions of the film; Figure 5 The optical morphology of the rectangular steel sheet material of the Al-Cr film prepared in Example 3 of the present invention and the sealing ring sample for the engine sealing system; Figure 6 This is a surface photograph of the thin Al-Cr film prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0022] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.
[0023] The present invention will be described in detail below with reference to the accompanying drawings and in conjunction with embodiments.
[0024] like Figure 1 As shown in the figure, Example 1 A method for preparing a fuel corrosion resistant Al-Cr film for an engine sealing system comprises the following steps: (1) Pretreatment of substrate: The polished 304 stainless steel substrate was ultrasonically cleaned in petroleum ether, ethanol and acetone for 15 minutes each, and then dried to obtain the pretreated substrate.
[0025] (2) Preparation of thin film: The film was deposited by unbalanced magnetron sputtering technology. The dried steel substrate sample was placed in the coating vacuum chamber, and the coating chamber was evacuated to a background vacuum better than 3×10 -3 When 2400 Å / s Pa, argon gas was introduced to perform Ar plasma pre-sputtering to clean the target and substrate surfaces and further remove surface impurities.
[0026] When pre-sputtering and cleaning the substrate, the argon gas flow rate is 30 sccm, the bias voltage is 200-400 V, the Al target current is 0.2 A, the Cr target current is 0.2 A, and the sputtering etching time is 30 min.
[0027] Then, the thin film deposition was carried out. First, the argon gas flow rate was 30sccm, the bias voltage was 80V, and the Al target current was initially 0.1~0.5A, which gradually increased to 0.6A after 20min. Then, after another 40min, the Al target current gradually increased to 1.8A. Finally, at the argon gas flow rate of 15sccm, the bias voltage of 80V, the Al target current was 2.2A, the Cr target current was 0.1A, and the total deposition time was 150min. The rotation speed of the turntable was 2 r / min.
[0028] After the deposition is completed, the sample is cooled to room temperature in a high vacuum coating chamber along with the furnace. In about 3 hours, an Al-Cr film can be obtained.
[0029] The surface and cross-sectional morphologies of the obtained Al-Cr films were characterized by FESEM microscopy. Figure 1 and 2 As shown in the figure, it can be seen that the structure of the film is relatively dense, the thickness is 2.7μm, and the atomic percentage of Cr on the surface of the film is 3%.
[0030] Example 2 A method for preparing a gas corrosion resistant Al-Cr film for an engine sealing system comprises the following steps: (1) Pretreatment of substrate: The pretreatment of the 9Cr18 steel substrate is the same as in Example 1, thereby obtaining a pretreated substrate.
[0031] (2) Film preparation: The thin film was deposited by magnetron sputtering technology. The dried 9Cr18 steel substrate sample was placed in a coating vacuum chamber, and the substrate was pre-sputtered and cleaned as in Example 1. Then, an Al-Cr thin film was prepared by sputtering deposition of an Al target and a Cr target.
[0032] Then, the thin film deposition was carried out. First, the argon gas flow rate was 30sccm, the bias voltage was 100V, and the Al target current was initially 0.2A, which gradually increased to 0.8A after 20min. Then, after another 40min, the Al target current was gradually increased to 2A. Finally, the argon gas flow rate was 20sccm, the bias voltage was 100V, the Al target current was 2A, the Cr target current was 0.2A, and the total deposition time was 300min. The rotation speed of the turntable was 1 r / min.
[0033] After the deposition is completed, the sample is cooled to room temperature in a high vacuum coating chamber along with the furnace. In about 4 hours, an Al-Cr film can be obtained.
[0034] The surface and cross-sectional morphologies of the obtained Al-Cr films were characterized by FESEM microscopy. Figure 2 As shown in the figure, it can be seen that the structure of the film is more compact, the thickness is 8.6 μm, and the atomic percentage of Cr on the surface of the film is about 4%.
[0035] The film / substrate bonding strength of the obtained Al-Cr film was tested by a scratch tester. Figure 3 As shown. The film / substrate bonding strength of Al-Cr films is greater than 30N. Test conditions: end load 30N, load loading speed 15N / min, scratch length 5mm. The scratch morphology was observed with an optical microscope, as shown Figure 4 As shown in the figure, at the end of the scratch test, the load was the largest, but the film in the scratch did not peel off, and there were no cracks on the sides and inner wall of the scratch, showing a smooth and flat surface. This shows that the film has good bonding and ductility with the steel substrate.
[0036] Example 3 A method for preparing a fuel corrosion resistant Al-Cr film for an engine sealing system comprises the following steps: (1) Pretreatment of substrate: The rectangular iron sheet and the sealing ring samples were ultrasonically cleaned in petroleum ether, ethanol and acetone for 20 minutes each, and then quickly dried to obtain the pretreated substrate.
[0037] (2) Preparation of thin film: The thin film is deposited by magnetron sputtering technology. The dried rectangular iron sheet and the sealing ring sample are fixed on a fixture and placed in a coating vacuum chamber. The substrate is pre-sputtered and cleaned as in Example 1.
[0038] During the film deposition, the film deposition parameters are the same as those in Example 2. After the deposition is completed, the sample is cooled to room temperature in a high vacuum coating chamber, and after about 5 hours, a rectangular iron sheet and a sealing ring sample with Al-Cr film deposited thereon can be obtained.
[0039] The prepared Al-Cr film has good uniformity on the surface of the rectangular iron sheet and the sealing ring sample, and the film / substrate bonding is firm.
[0040] The Al film was prepared by unbalanced magnetron sputtering technology, and the gradient component deposition method was used to fundamentally solve the technical problems of poor bonding and loose structure of Al film on steel substrate. In the process of film preparation, the bombardment energy of the target material and the diffusion capacity of the deposited atoms were effectively regulated by orderly and reasonable regulation of the deposition parameters, which increased the nucleation density of the deposited atoms and thus increased the density of the film. The Cr element also has excellent corrosion resistance. A small amount of Cr element is doped in the Al film, which makes the film show good ductility and improves the sealing effect of parts. The Al-Cr film prepared by the present invention has a Cr content of 1~6 at.%, a thickness of about 2~9μm, and has high film / substrate bonding strength (≥30 N), good ductility and excellent fuel corrosion resistance. This overcomes the main shortcomings of Al film materials on steel substrates, such as easy peeling and high brittleness, and provides certain technical support for the film formation and application of aluminum alloy materials. It has important application prospects in corrosion-resistant sealing and lubrication in engine fuel systems.
[0041] Comparative Example 1 The difference from Example 1 is that: the gradient composition deposition is not used, the argon gas flow rate is 15 sccm, the bias voltage is 80 V, the Al target current is 2.2 A, the Cr target current is 0.1 A, and the total deposition time is 150 min. Figure 6 shown.
[0042] The role of the gradient component deposition is to promote the densification of the film structure, and at the same time, it can improve the bonding strength between the Al-based film and the substrate. If the gradient deposition is not used, the direct deposition method is used, and the results are as shown in Comparative Example 1 ( Figure 6 It can be seen that the Al-based film grows on the surface of the steel substrate with a loose structure. This film has a poor bond with the substrate and is easy to fall off.
[0043] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing an Al-Cr thin film material resistant to fuel oil corrosion, characterized in that: The following steps are involved: S1: pre-treating the substrate; S2: Deposition of thin film by unbalanced magnetron sputtering technology: Under vacuum conditions, pre-sputtering is performed with Ar plasma to clean the target and substrate surfaces, followed by sputtering deposition of Al and Cr targets to a preset film thickness, followed by furnace cooling to room temperature to prepare an Al-Cr film.
2. The method for preparing a fuel oil corrosion resistant Al-Cr thin film material according to claim 1, characterized in that: The pretreatment of the substrate in step S1 includes ultrasonic cleaning and drying the surface of the steel substrate.
3. The method for preparing a fuel oil corrosion resistant Al-Cr thin film material according to claim 1, characterized in that: The pretreatment of the substrate in step S1 includes polishing the substrate. The polished steel substrate is ultrasonically cleaned in petroleum ether, ethanol and acetone respectively and then dried.
4. The method for preparing a fuel oil corrosion resistant Al-Cr thin film material according to claim 1, characterized in that: The substrate includes one of stainless steel and 9Cr18 steel.
5. The method for preparing a fuel oil corrosion resistant Al-Cr thin film material according to claim 1, characterized in that: In step S2, two Al targets and one Cr target disposed face to face are used to deposit the thin film by unbalanced magnetron sputtering technology, and the purity of the target materials is not less than 99.99%.
6. The method for preparing a fuel oil corrosion resistant Al-Cr thin film material according to claim 1, characterized in that: In step S2, Ar plasma is used for pre-sputtering cleaning of the target and substrate surface, with an argon gas flow rate of 20-30 sccm, a bias voltage of 200-400 V, an Al target current of 0.2-0.4 A, a Cr target current of 0.1-0.3 A, and a sputtering cleaning time of 30 min.
7. The method for preparing a fuel oil corrosion resistant Al-Cr thin film material according to claim 1, characterized in that: During film deposition, a gradient composition deposition method was used. The argon gas flow rate in the first stage was 25~40sccm, the bias voltage was 80~140V, and the Al target current was initially 0.1~0.5A, which gradually increased to 0.6~1A after 15~40min. After another 40 to 80 minutes, the Al target current in the second stage gradually increased to 1.5 to 3 A. In the third stage, the film is deposited to a preset thickness at an argon gas flow rate of 10-30 sccm, a bias voltage of 80-140 V, an Al target current of 1.5-2.8 A, and a Cr target current of 0.1-1 A; Preferably, the preset thickness is 2-9 μm.
8. The method for preparing a fuel oil corrosion resistant Al-Cr thin film material according to claim 1, characterized in that: After the deposition is completed, the sample is cooled to room temperature in the high vacuum coating chamber with the furnace, and the cooling time is 3 to 5 hours.
9. A fuel corrosion resistant Al-Cr film prepared by the method for preparing a fuel corrosion resistant Al-Cr film material according to any one of claims 1 to 8, characterized in that: The Cr content in the fuel corrosion resistant Al-Cr film is 1~6 at.%, and the film-base bonding strength of the fuel corrosion resistant Al-Cr film is ≥30 N; Preferably, the fuel oil corrosion resistant Al-Cr film has a thickness of 2-9 μm and a microhardness of Hv100-200.
10. The fuel corrosion resistant Al-Cr film according to claim 9 is applied to an engine sealing system.